Nursing experience of a patient with insomnia treated by acupoint massage combined with ginger-partitioned moxibustion (穴位按摩联合隔姜灸治疗失眠1例的护理体会) - LIU Cui (刘翠); ZHEN Ruiwen (郑睿文); ZHOU Hui (周慧); ZHAO Jin (赵锦); TANG Ling (唐玲); CHEN Hong (陈宏) (Association of Integrative Nursing, 2022)
This paper reviewed the clinical data of a patient with sleep disorder caused by insomnia. Based on the psychological, physical and social assessment, the Traditional Chinese Medicine techniques acupoint massage combined with ginger-partitioned moxibustion were conducted to improve the sleep quality of the patient. Comprehensive nursing interventions such as basic nursing, dietary management, emotional care were carried out during the treatment. (本文回顾1例因失眠导致睡眠紊乱患者的临床资料, 总结穴位按摩联合隔姜灸的干预效果和相关护理经验。在心理、生理、社会评估的基础上, 医护人员采用中医特色护理技术穴位按摩联合隔物灸进行干预, 同时配合实施常规护理、饮食护理、情志护理等综合干预措施, 有效改善患者失眠症状。)